New P–T and U–Pb constraints on Alpine Schist metamorphism in south Westland, New Zealand - Scott, J.; Auer, A.; Muhling, J.; Czertowicz, T.; Cooper, A.; Billia, M.; Kennedy, Allen (2015)
Metamorphic mineral compositions of a staurolite-bearing greyschist from the middle reaches of the Moeraki River valley in south Westland reveal peak equilibration at c. 558 ± 50 °C and c. 6.1 ± 1.2 kbar. Two c. 83 Ma U–Pb monazite age populations from the cores of monazite-apatite-allanite-epidote corona structures in mylonitised schists from near Fox Glacier confirm that Alpine Schist metamorphism occurred during the Late Cretaceous. The published spread in Late Cretaceous metamorphic ages indicates that metamorphism was diachronous or was a protracted event. Further dating is required to pin down the cryptic transition into the Jurassic–Early Cretaceous metamorphosed Otago Schist, but the Alpine Schist must extend at least 11 km east of the Alpine Fault in south Westland and overprint the suture between the Pounamu and Rakaia terranes. The P–T–t results imply that the Late Cretaceous crust represented by portions of the Alpine Schist was probably of similar thickness to that beneath the Southern Alps today, but with dehydration and partial melting occurring near the base. The crust under Westland and Otago may be dry and therefore strong.